Molecular Modulation of Prefrontal Cortex: Rational Development of Treatments for Psychiatric Disorders. - Gamo, Nao J.; Arnsten, Amy F. T. (Behavioral Neuroscience, 2011)
Dysfunction of the prefrontal cortex (PFC) is a central feature of many psychiatric disorders, such as attention deficit hyperactivity disorder (ADHD), posttraumatic stress disorder (PTSD), schizophrenia, and bipolar disorder. Thus, understanding molecular influences on PFC function through basic research in animals is essential to rational drug development. In this review, we discuss the molecular signaling events initiated by norepinephrine and dopamine that strengthen working memory function mediated by the dorsolateral PFC under optimal conditions, and weaken working memory function during uncontrollable stress. We also discuss how these intracellular mechanisms can be compromised in psychiatric disorders, and how novel treatments based on these findings may restore a molecular environment conducive to PFC regulation of behavior, thought and emotion. Examples of successful translation from animals to humans include guanfacine for the treatment of ADHD and related PFC disorders, and prazosin for the treatment of PTSD. Reprinted by permission of the publisher.